2011
DOI: 10.4103/1658-354x.76473
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of efficacy of esmolol and fentanyl for pressure attenuation during laryngoscopy and endotracheal intubation

Abstract: Objective:To compare the effectiveness of single bolus dose of esmolol or fentanyl in attenuating the hemodynamic responses during laryngoscopy and endotracheal intubation.Methods:Ninety adult ASA I and ASA II patients were included in the study who underwent elective surgical procedures. Patients were divided into three groups. Group C (control) receiving 10 ml normal saline, group E (esmolol) receiving bolus dose of esmolol 2 mg/kg and group F (fentanyl) receiving bolus dose of fentanyl 2 µg/kg intravenously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 10 publications
2
26
0
4
Order By: Relevance
“…Fentanyl suppresses the haemodynamic response by increasing the depth of anaesthesia and decreasing the sympathetic discharge. 26 Similar to our study Ayse Mizrak and et al found neither fentanyl nor local infilteration of lidocaine 2% scalp block alone could effectively suppress the MAP 9 but, the combined use of both the drugs was able to suppress the MAP after pin fixation.…”
Section: Discussionsupporting
confidence: 89%
“…Fentanyl suppresses the haemodynamic response by increasing the depth of anaesthesia and decreasing the sympathetic discharge. 26 Similar to our study Ayse Mizrak and et al found neither fentanyl nor local infilteration of lidocaine 2% scalp block alone could effectively suppress the MAP 9 but, the combined use of both the drugs was able to suppress the MAP after pin fixation.…”
Section: Discussionsupporting
confidence: 89%
“…However increased in heart rate was more in Group F as compare to Group D.This increase was highly significant (p<0.001). These observations are comparable to those by Martina Ahoet al 8 , Sukhminderjit Singh Bajwa et al 32 , N. Turgut et a 22 . However Sukhminderjit Singh Bajwaet al 32 used Dexmedetomidine in dose of 1 µg/kg and N. Turgut et al 22 used Fentanyl in dose of 1 µg/kg.…”
supporting
confidence: 89%
“…Our results coincide with a study conducted by Gupta and Tank et al, Parida S et al who used Fentanyl 2 μg/kg intravenously slowly 3 min before induction of anesthesia to attenuate the pressor response to laryngoscopy and intubation. 11,20 Withington PS et al found that the heart rate was consistently higher but not statistically significant after NTG infusion during Fentanyl, thiopentone, pancuronium anaesthesia in coronary artery bypass graft surgery. 21 Ebert JP et al reported Fentanyl intravenously decreased heart rate below baseline and maintained it there.…”
Section: Haemodynamic Variablesmentioning
confidence: 99%
“…9 Fentanyl citrate, an opioid is a phenylpiperidine of the 4-aminopiperidine series structurally related to pethidine and controls both heart rate and blood pressure responses. 10,11 However, Fentanyl can produce complex respiratory depression and truncal rigidity at higher doses. Administration of NTG alone during preintubation may not be sufficient to completely mediate hemodynamic response due to the tendency of Nitroglycerine to produce tachycardia.…”
Section: Introductionmentioning
confidence: 99%